2016
DOI: 10.1186/s12966-016-0421-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plain packaging, warning labels, and taxes on young people’s predicted sugar-sweetened beverage preferences: an experimental study

Abstract: BackgroundConsumption of sugar-sweetened beverages (SSBs) is associated with increased risk of obesity, diabetes, heart disease and dental caries. Our aim was to assess the effects of plain packaging, warning labels, and a 20 % tax on predicted SSB preferences, beliefs and purchase probabilities amongst young people.MethodsA 2 × 3 × 2 between-group experimental study was conducted over a one-week period in August 2014. Intervention scenarios were delivered, and outcome data collected, via an anonymous online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 26 publications
3
122
2
3
Order By: Relevance
“…These proposed regulations have the potential to substantially alter the Brazilian food supply as well as consumers' understanding, perceptions, purchase intentions, and intake of UPF. A recent randomized controlled trial in Brazil found that the exposure to FoP warning labels that only identify unhealthy foods helped consumers understand the unhealthiness of UPF and reduced their intentions to purchase this food [8], consistent with a growing body of literature that shows that warning labels improve consumers' ability to assess the healthfulness of products [10,11] and help them make healthier choices [12][13][14][15]. Conversely, nutrition and health claims have been shown to make consumers think a product is healthier than it actually is, working as a marketing strategy rather than an information tool (i.e., the "health halo" effect) [16,17].…”
Section: Introductionmentioning
confidence: 59%
“…These proposed regulations have the potential to substantially alter the Brazilian food supply as well as consumers' understanding, perceptions, purchase intentions, and intake of UPF. A recent randomized controlled trial in Brazil found that the exposure to FoP warning labels that only identify unhealthy foods helped consumers understand the unhealthiness of UPF and reduced their intentions to purchase this food [8], consistent with a growing body of literature that shows that warning labels improve consumers' ability to assess the healthfulness of products [10,11] and help them make healthier choices [12][13][14][15]. Conversely, nutrition and health claims have been shown to make consumers think a product is healthier than it actually is, working as a marketing strategy rather than an information tool (i.e., the "health halo" effect) [16,17].…”
Section: Introductionmentioning
confidence: 59%
“…This study has important research and policy implications. There is convincing evidence on the effects of population prevention strategies and interventions aimed at reducing high sugar in population diets 54–57 . However, the problem of high sugar intake continues to persist worldwide, suggesting either that strategies or interventions are not effective, or that interventions likely to have an impact on consumption levels have not been implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Although plain packaging has most prominently been used as an intervention to reduce tobacco consumption, the introduction of plain packaging could also be an effective way to reduce consumers' purchase of other products where salient cues are present on product packaging, such on sugar-sweetened drinks (Bollard et al 2016; Figure 1). …”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%